Analisis Faktor-Faktor yang Mempengaruhi Likuiditas Pasar Saham - Natsir, Khairina; Bangun, Nurainun; Waani, Alfredo Marthen (Jurnal Ekonomi, 2023)
The objective of this study is to obtain valid evidence regarding the individual effects of the variables Firm Value, earnings management, and stock risk on stock market liquidity. Stock Liquidity, Earning Management, Firm Value, and Stock Risk are measured respectively by Total Volume Activity, discretionary accrual model modified Jones, PBV, and Beta. Research in the form of causality. Samples were selected using a purposive technique. The data is extracted from the company's annual financial reports accessed from official sources. The samples were 16 companies from the infrastructure sub-sector manufacturing group listed on the IDX during the 2017-2021 period, so that 80 observation data were obtained. Multiple regression is used for data analysis, where the tests include multicollinearity tests, partial-t tests and coefficient of determination tests. The findings of this study show that Earning Management, Firm Value, and Stock Risk affect Stock Market Liquidity